A Melanoma Epidemic in Iceland: Possible Influence of Sunbed Use - Héry, Clarisse; Tryggvadóttir, Laufey; Sigurdsson, Thorgeir; Ólafsdóttir, Elínborg; Sigurgeirsson, Bardur; Jonasson, Jon G.; Olafsson, Jon H.; Boniol, Mathieu; Byrnes, Graham B.; Doré, Jean-François; Autier, Philippe (American Journal of Epidemiology, 2010)
Since 1980, sunbed use and travel abroad have dramatically increased in Iceland (64°–66°N). The authors assessed temporal trends in melanoma incidence by body site in Iceland in relation to sunbed use and travel abroad. Using joinpoint analysis, they calculated estimated annual percent changes (EAPCs) and identified the years during which statistically significant changes in EAPC occurred. Between 1954 and 2006, the largest increase in incidence in men was observed on the trunk (EAPC = 4.6%, 95% confidence interval: 3.2, 6.0). In women, the slow increase in trunk melanoma incidence before 1995 was followed by a significantly sharper increase in incidence, mainly among women aged less than 50 years, resembling an epidemic incidence curve (1995–2002: EAPC = 20.4%, 95% confidence interval: 9.3, 32.8). In 2002, the melanoma incidence on the trunk was higher than the incidence on the lower limbs for women. Sunbed use in Iceland expanded rapidly after 1985, mainly among young women, and in 2000, it was approximately 2 and 3 times the levels recorded in Sweden and in the United Kingdom, respectively. Travels abroad were more prevalent among older Icelanders. The high prevalence of sunbed use probably contributed to the sharp increase in the incidence of melanoma in Iceland.